Impact of the application of the glo bal GAP norm, in the Latin American Agro-food sector - Rincón Parra, Nidia Stella; Figueredo, César Augusto; Salazar Villamil, Nubia Stella (Revista Colombiana de Investigaciones Agroindustriales, 2015)
The tendency of the global markets has undergone changes in variables, that define demand, because it is dependent to the transformation of the consumption habits, which are pointed to innocuous and sustainable products. In consistency, the impact of the Global GAP norm application was identified in the Latin-American Agro-food Sector, from the classification of the innocuousness food assurance, the actions to promote the safety and health of the workers, moreover of the guided management to reduce the environmental impact and strengthen the sustainability of the natural resources. The research took as an object population for study, published case, about the acquired experiences on the implementation of this regulation on the fruit and vegetable productive sector in Latin America. 27 cases were taken for bibliographic review, which were selected from the year 2007, when it acquired the name Global GAP, the need for expansion to new markets became evident and an urgent requirement of support and product recognition. As evaluative criterions the three pillars that are based on were taken in account. Out of the results obtained, one of the most relevant is the one that establishes that for the different productive sectors it is important to achieve product certification as a competitive strategy; however, it is important to raise awareness of is essential to be aware in giving the same importancelevels for its application in the innocuousness aspects, the safety and the health of the workers and risk management of the environmental impact. Para citar este artículo Rincón, N., Figueredo, C. y Salazar, N. (2015). Impacto de la aplicación de la norma GlobalGAP, en el sector agroalimentario Latinoaméricano. Rev. Colomb. Investig. Agroindustriales, 2(1), 84-97. DOI: http://dx.doi.org/10.23850/24220582.173